Communication Strategies in the 2020 Local Election Stages Socialization During the Covid-19 Pandemic - Ni Made Ras Amanda Gelgel; Kadek Dwita Apriani; Richard T Ginting (Ikatan Sarjana Komunikasi Indonesia, 2020)
Indonesia has decided to hold simultaneous local elections on December 9, 2020, even though the country and the rest of the world still face the COVID-19 pandemic. The local election stages have begun in June 2020 by forming a unit to update data of voters and socialize how to hold the elections during the pandemic. This paper aims to build communication strategies in socializing how to hold the elections during the COVID-19 pandemic. The results were obtained using the survey method involving 440 respondents in Denpasar in September 2020. The communication strategy is a combination of offline and online mediums. Despite a policy to stay at home, data shows that residents of Denpasar still needed offline mediums such as billboards and banners. In addition, they also searched for information about the election through printed advertisements and television advertisements. To ensure the smooth socialization of election process, the General Election Commission (KPU) in Denpasar uses accounts in social media platforms such as Instagram and Facebook in collaboration with parties that have a large number of followers or mass media that have accounts in social media with a large number of followers. However, almost all respondents do not follow the official account of KPU Denpasar. Uniquely, in Denpasar, some potential voters still rely on community leaders and figures in searching for information about the local election. To that end, to build communication strategies, these community leaders and figures should be involved. Data also show that online meeting like zoom, google meet, or Webex meeting is not sufficient.